On a student skill of responding to spoken messages. An attempt at diagnosing the problem - Chyb-Winnicka, Marta (Papers in Linguistics, 2023)
This article attempts to determine to what extent primary school students have mastered the skill of responding to spoken messages, i.e. a competence allowing them to listen actively and effectively, which is necessary in private and professional life. To achieve the research aim, the author carried out empirical research among two groups: 190 fourth and 159 eighth graders who attend eight primary schools in Opole. The research tool was a listening test in Polish as a native language: a part of an interview and two test tasks. The conducted research shows that the participants have developed the ability to respond to spoken messages at a low level. The results prompted the author to conclude that the present-day schooling does not prepare students to listen actively and effectively in natural communication circumstances.